The impact of local and foreign automation on labor market outcomes in emerging countries - Luis R. Diaz Pavez; Inmaculada Martínez-Zarzoso (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2021)
In the XXI century, the labor market effects of automation have gained significant attention from scholars and policymakers alike. Concerns about potential negative effects are particularly relevant in emerging countries, where a rapid acceleration of robot adoption and an increasing involvement in global value chains has been observed in recent years, with the subsequent increase in exposure to foreign competition. This paper estimates the effect of local and foreign robots on labor market outcomes and labor shares using a panel dataset composed of 16 sectors and ten emerging countries from 2008 to 2014. The endogeneity of robots' adoption is addressed with an instru- mental variable approach and using a shift-share index of exposure to foreign robots. When all sectors are considered, the main results show that only foreign robot adoption, but not local, has affected employment, whereas no effects on the labor share are found. When exploring sectoral heterogeneity, we find that the foreign robots' effect on employment has mainly occurred in the agricultural and industrial machinery sectors, the former being driven by a reduction of offshoring and affecting nearly 60% of jobs in emerging countries.
Keywords: J23; O33; F16; 330; Automation; Labor markets; Inequality; Emerging countries